HUBUNGAN PERNIKAHAN JARAK JAUH (LONG DISTANCE MARRIAGE) DENGAN STRES KERJA PADA KARYAWAN PT WIJAYA KARYA (PERSERO) TBK (PROYEK PEMBANGKIT LISTRIK TENAGA MESIN GAS 50 MW SUMBAWA) - Budi Purwanto; Ivon Arisanti; Ayuning Atmasari (JURNAL PSIMAWA, 2019)
This research aims to know the relationship between long distance marriage and working stress on employees at PT Wiijaya Karya (a project of gas engine power plant 50 MW Sumbawa). This research use correlative quantitative method and psychology scale as an instrument to collecting data. That is likert scale, which it means scale long distance marriage based on aspects couple relationship and working stress based on aspects working stress that had been compiled by the researcher. The result of this research show that there is a positive correlation and the significance between long distance marriage and working stress of employee by value correlation of co-efficient 0,576 and p by 0,0001 / p < 0,05 which is mean the higher employees’ long distance marriage, so the higher employees’ working stress and vice versa. The lower employees’ long distance marriage, so the lower employees’ working stress.